On the identity of Opuntia elata s.l. (Cactaceae) introduced in the Mediterranean region. A taxonomic and nomenclatural update - Aymerich, Pere; Font, Fabián (Mediterranean Botany, 2023)
Opuntia elata and O. monacantha are the two species of Opuntia Series Armatae traditionally accepted as naturalized in the Mediterranean region and Europe. However, a review based on the analysis of the available images and on the criteria of the most recent taxonomic proposals shows that O. elata s.s. is not present. The plants so far assigned to O. elata belong to O. bonaerensis, a clearly differentiated species, or to O. rioplatensis and O. canterae, both species similar to O. elata and recently segregated. The situation looks similar for South Africa and Australia, where the iconography shows other species of this group but not O. elata in the strict sense.